Orbital Myiasis: An Unusual Presentation of Retinoblastoma - Minhaz M. Karkhanawala; Urvi J. Patel; Mehul Patel; Hansa H. Thakkar (Delhi Journal of Ophthalmology)
A two year old child, presented with parents complaining of maggots with fungating mass in the right eye for two months. On examination, the child was debilitated. He had no perception of light in the right eye and only perception of light in the left eye. The right eye had a huge fungating mass invaded by maggots along with blood clots. The left eye had leukocoria. Ultrasonography of the right eye was not possible due to fungating mass and that of the left eye showed an intraocular mass with calcification. Diagnosis of bilateral retinoblastoma was made. Maggots were removed from the right eye after instillation of lignocaine and turpentine oil. Magnetic resonance imaging suggested extensive mass with cerebral metastasis. Systemic antibiotics, antifungal agents, palliative external beam radiotherapy followed by chemotherapy were given which led to reduction in tumor mass and improvement in the general condition. The mass in the left eye also demonstrated regression. Orbital myiasis in this case was a result of lack of awareness and negligence.